(untitled) (Journal of Parents and Teachers, 2014)
Obesity has ceased to be an aesthetic problem to become a real health problem in today’s society. This article seeks to raise awareness about this problem and talks about the habits, about education, that we have to carry out and that, to this day, we are not taking on this issue is concerned.